Fearless - Pascal, Francine (Simon Pulse, 2012)
Gaia Moore is brilliant and beautiful. She's trained in three kinds of martial arts, has a reflux speed that's off the charts, and can break codes in four languages. She's also missing the fear gene. All Gaia wants is to be like everyone else. Instead, she's left wondering about her past, her missing family--and the unavailable boy she's falling for. But everything changes when she learns that someone is hunting her down for her special skills, and they'll do anything to get to her.